Through-the-scope clip with anchor prongs for defect closure following myotomy, resection, anti-reflux mucosectomy, fistula management, or bleeding - Mosko, Jeffrey D.; Al-Haddad, Mohammad; Pohl, Heiko; Kumta, Nikhil A.; Chan, Shannon Melissa; Ryou, Marvin; Nabi, Zaheer; Zhou, Ping-Hong; Inoue, Haruhiro; Peetermans, Joyce A.; Rousseau, Matthew J.; von Renteln, Daniel (Endoscopy International Open, 2026)
Through-the-scope endoscopic clips (TTSCs) are essential for defect closure. A newly designed TTSC with anchor prongs can close defects that were challenging with standard TTSCs. We assessed the safety and efficacy of the TTSC with anchor prongs.We prospectively studied defect closure using a TTSC with anchor prongs within a multicenter cohort study at 10 sites in six countries. Outcomes were rates of complete defect closure, delayed bleeding, and device- or procedure-related serious adverse events (SAEs).Fifty lesions among 49 participants were studied. Mean age was 55.6 ±16.6 years, and 24 (49.0%) were male. Indications for closure included endoscopic myotomy procedures (n = 21 lesions, 42.0%), bleeding (n = 9, 18.0%), full-thickness resection (n = 7, 14.0%), submucosal tunneling endoscopic resection (n = 6, 12.0%), endoscopic antireflux mucosectomy (n = 3, 6.0%), perforation or closure of non-bleeding fistula (n = 2, 4.0%), and defect closure after removal of embedded plastic biliary stent (n = 2, 4.0%). Complete defect closure was achieved in 49 lesions (98.0%). No delayed bleeding occurred 30 days after the index procedure. Three patients (6.0%) had four related SAEs: ischemic colitis in a participant with a bleeding colonic fistula (1), submucosal leak in a peroral endoscopic myotomy (POEM) procedure (1), and septic shock and mucosal injury associated with a gastric POEM procedure (1). All related SAEs resolved by 10 days after onset.The newly designed TTSC with anchor prongs demonstrated safety and efficacy in defect closures after submucosal interventions, with high rates of successful defect closure and no delayed bleeding. (ClinicalTrials.gov number, NCT05653843)
Keywords: Endoscopy Upper GI Tract; POEM; Motility/achalasia; Non-variceal bleeding